Critical Evaluation of Silicon Nitride Powder Characterization and its Effects on Injection Molding - S. G. Malghan; V. K. Pujari (Society for Mining, Metallurgy & Exploration, 1990)
Detailed characterization of all the powder constituents during powder processing is necessary for the reproducible manufacture of ceramic components that will perform reliably in intended applications. In this paper, selected physical and surface chemical techniques for characterization of silicon nitride powder are evaluated. The characterization data are discussed in the context of how these data, through their influence on powder processing unit operations, can affect the final microstructure. In the forming of ceramics, some of the major variables of injection molding are evaluated. Accurate measurement and control of these variables is emphasized for manufacture of Si3N4 ceramics with a high degree of reliability.